Policy related attitude surveys - assumptions and significance - Davis, Ee; Sinnott, R (Economic & Social Studies, 1982)
Precis: The article first considers a recent argument which rejects policy related attitude research on the grounds that it relies on four assumptions which are said to be untenable. In examining each of the assumptions we show that they are not in fact prerequisites of the approach and suggest what the actual assumptions are in each area. The article then takes up the broader issue of the significance of individual attitudes. This issue is considered in general and in terms of a specific example drawn from the results of the .1981 General Election in the Republic of Ireland. The conclusion is drawn that attitudes are sufficiently relevant to the policy process to fully justify the agenda of applied attitude research.
Keywords: Economics; Sociology